Endometriosis can cause gastric obstruction - Sawera Tahir; Muhammad Ilyas; Jaber Gasem (European Journal of Case Reports in Internal Medicine)
Introduction: Gastric outlet obstruction is commonly associated with malignancies and benign conditions such as peptic ulcer disease and Crohn’s disease. This report presents an uncommon instance of gastric endometriosis leading to gastric outlet obstruction, a condition that should be considered in the differential diagnosis. Case description: A 37-year-old female presented with persistent postprandial vomiting occurring approximately 30 minutes after meals, along with significant weight loss of 25.4 kg over 2.5 months. Her medical history included a subtotal colectomy with ileo-distal sigmoid anastomosis for slow transit constipation and a total abdominal hysterectomy with bilateral salpingo-oophorectomy for endometriosis. Clinical examination revealed abdominal tenderness and a vague epigastric mass. An abdominal CT scan identified a 5 cm mass arising from the pylorus and duodenal wall, with associated pathological lymph node enhancement. Despite multiple endoscopic biopsies, histological results were non-diagnostic due to the submucosal nature of the lesion; technical limitations prevented the capture of endoscopy images. Due to the severity of symptoms and a strong clinical suspicion of a gastrointestinal stromal tumour (GIST), the patient underwent a Whipple’s resection. Histopathological analysis of the resected specimen unexpectedly confirmed gastric endometriosis. Conclusion: This case highlights the need to consider endometriosis in the differential diagnosis of gastric outlet obstruction, particularly in women with a history of endometriosis or prior gynaecological surgeries. The discrepancy between imaging findings and negative biopsy results underscores the limitations of standard endoscopic biopsy in diagnosing submucosal lesions. Endoscopic ultrasound-guided biopsy or laparoscopic biopsy should be considered when standard biopsies are non-diagnostic. Early recognition of this rare condition can prevent delays in treatment and improve patient outcomes.